FUNGSI SOSIAL BAHASA TAGAR #SEMUAHARUSVAKSIN DI MEDIA SOSIAL TWITTER - Siti Khoerun nisa; Retno Purwani Sari (Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2021)
ABSTRACT The presence of social media has become one of the tools that can be used by the public to express their opinions regarding the phenomena that occur around them. One of these forms of opinion delivery was conveyed during a pandemic which required all elements to inform each other of the importance in maintaining health protocols and vaccination programs. Twitter with its hashtag feature allows the public to disseminate information about vaccinations and massive invitations to the public. Due to the increasingly massive use of social media to deliver the messages, this study analyzes languages involving in the hashtag #semuaharusvaksin to prove that they must convey specific function to play in digital social interaction. It describe the types of language functions based on Jakobson’s theory. This method used was descriptive qualitative. The data collection used documentation techniques, then the writer observed the utterances of netizens so that a comprehensive analysis were produced. The language functions found are referential, conative, conative-referential and phatic-referential functions. These findings may facilitate public knowledge to respond the tweet properly.